Intermediate language in the subtitle translation of Le Grand Voyage film into Indonesian Perjalanan Agung - Cholsy, Hayatul (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
This study aimed to explore the role of intermediate language in translating the dialogue subtitle of Le Grand Voyage film from French as source language into Indonesian as target language. This study used intermediate language translation theory from Amal Al Shunnaq (2019), which was a translating process from source language into target language through other foreign language. Le Grand Voyage film is a film with religious nuance with the life of maghrébin immigrants in France as the background. The film subtitle in Indonesian were translated from English subtitle which were previously translated from French dialogue. English as the intermediate language had a very important role since it determined the subtitle translation final result in the target language. In addition to economic reasons, the role of an intermediate language was to be able to simplify or make subtitle in target language more concise, therefore it could easily adjust the space and time on the screen display, refine the translation result so that the film subtitle in target language becomes more polite, such as the loss of swear words, and determines the message from source language into target language due to cultural influences and the peculiarities of the intermediate language.